4-Chloro-2-[(4-phenylthiazol-2-yl)hydrazonomethyl]phenol: a polymorph with Z?=2 - Dag, Cemile; Pasaoglu, Humeyra; Yuksektepe, Cigdem; Cukurovali, Alaaddin; Murat, Ebru (Int Union Crystallography, 2006)
The title compound, beta-C16H12ClN3OS, crystallizes with two independent molecules in the asymmetric unit, both of which show a similar twisted conformation. It is polymorphic with alpha-C16H12ClN3OS [Caliskan, Dag, Yuksektepe, Cukurovali & Murat (2006). Acta Cryst. E62, o4889 - o4890]; both forms crystallize in the same space group. The two independent molecules in beta-C16H12ClN3OS are linked into dimers by pairs of N-H center dot center dot center dot N hydrogen bonds.